Penggabungan Digital Printing Hijab Motif Endek Dengan Tie Dye Eksplorasi Gaya Busana Muslimah - Shafa, Naura Taqyna; Adnyana, I Wayan; Karja, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
The use of Muslim clothing, especially in using hijab, has become an art trend carried out by a fashion connoisseur. Uniqueness in terms of motifs contained in the hijab can be used as a fashion item that is often used. In this case, the motif used in the hijab is designed using endek motifs with coloring using tie dye techniques that can add aesthetics to clothing and fashion lovers and the public can get to know more about endek motifs, and can preserve the culture that comes from their respective regions. The process of creating this work uses technology that can facilitate the next process, namely by using digital printing technology on the hijab cloth that has been designed through the process of experimentation, exploration, and observation. The use of endek motifs in hijab design emphasizes several motifs in endek woven fabric. The resulting works are 6 (six) hijab works that have been printed using endek motifs and the results with coloring using tie dye coloring techniques which have their own uniqueness with coloring results that can be intentional or unintentional. The final result of this work is expected to encourage the community in preserving and disseminating their culture, can increase the diversity of motif designs on the hijab, especially in traditional motifs, can help in the needs of dressing, especially in Muslim clothing, and can provide a variety of hijab designs, and can give a new impression to the connoisseurs of Muslim fashion.